Examining the Effectiveness of Mnemonics Serious Games in Enhancing Memory and Learning: A Scoping Review - Kingson Fung; Kiemute Oyibo (Applied Sciences)
Mnemonics hold potential for promoting long-term memory. Hence, they are being leveraged in serious games aimed to support long-term retention and retrieval of information. However, there is limited work focused on synthesizing the published research and findings on mnemonics serious games with a view to uncovering the extent of their application and effectiveness. This scoping review aims to bridge this gap. Articles were retrieved from four databases (ACM Library, IEEE Xplore, Scopus, and Web of Science). The criteria for inclusion were that the papers must be user studies that focused on mnemonics and serious games at the same time, were written in English, and were published in peer-reviewed journals or conferences. Two researchers, with the guidance of a senior researcher, independently and collaboratively assessed the eligibility of the retrieved papers using the PRISMA flowchart, elicited the relevant data, and tabulated the results in tables and charts using the GPS (game play, purpose, and scope) model. There were 12 papers that were accepted in this scoping review. Overall, most of the mnemonics serious games had a positive effect on memory, suggesting that they hold potential for promoting long-term memory, especially in memorization-intensive instructions, where a good number of students still struggle to retain taught material due to pedagogical, personal, and social challenges. However, more research still needs to be conducted, especially in the area of player-created mnemonics and teaching users how mnemonics can be effectively created using visualization and elaboration techniques.